Assessment of continuous pain in newborns admitted to NICUs in 18 European countries. (17th April 2017) - Anand, Kanwaljeet J. S.; Eriksson, Mats; Boyle, Elaine M.; Avila‐Alvarez, Alejandro; Andersen, Randi Dovland; Sarafidis, Kosmas; Polkki, Tarja; Matos, Cristina; Lago, Paola; Papadouri, Thalia; Attard‐Montalto, Simon; Ilmoja, Mari‐Liis; et al.
Abstract: Aim: Continuous pain occurs routinely, even after invasive procedures, or inflammation and surgery, but clinical practices associated with assessments of continuous pain remain unknown. Methods: A prospective cohort study in 243 neonatal intensive care units (NICUs) from 18 European countries recorded the frequency of pain assessments, use of mechanical ventilation, sedation, analgesia or neuromuscular blockade for each neonate for up to 28 days after NICU admission. Results: Only 2113 of 6648 (31.8%) of neonates received assessments of continuous pain, occurring variably among tracheal ventilation (TrV, 46.0%), noninvasive ventilation (NiV, 35.0%) and no ventilation (NoV, 20.1%) groups (p < 0.001). Daily assessments for continuous pain occurred in only 10.4% of all neonates (TrV: 14.0%, NiV: 10.7%, NoV: 7.6%; p < 0.001). More frequent assessments of continuous pain occurred in NICUs with pain guidelines, nursing champions and surgical admissions (all p < 0.01), and for newborns <32 weeks gestational age, those requiring ventilation, or opioids, sedatives‐hypnotics, general anaesthetics (O–SH–GA) (all p < 0.001), or surgery (p = 0.028). Use of O–SH–GA drugs increased the odds for pain assessment in the TrV (OR:1.60, p < 0.001) and NiV groups (OR:1.40, p < 0.001). Conclusion: Assessments of continuous pain occurred in less than one‐third of NICU admissions and daily in only 10% of neonates. NICU clinical practices should consider including routine assessments of continuous pain in newborns. Abstract :